Community-based ecotourism: beyond authenticity and the commodification of local people. Issue 3 (3rd July 2018) - Pookhao Sonjai, Nantira; Bushell, Robyn; Hawkins, Mary; Staiff, Russell
ABSTRACT: Community-based ecotourism (CBET) aims to empower local communities through participation. Thailand is a good example of a developing country where the local community requires long-term support from stakeholders for empowerment. Given that the inauthenticity and commodification of CBET have yet to be discussed in terms of the influences of policy and external stakeholders, this research connects the missing link in the literature between policy, tourism stakeholders and practices in relation to the authenticity and commodification of CBET. In order to gain an understanding of the policy related to the CBET operation, central Thai government agencies and related non-governmental organisations (NGOs) participated in in-depth interviews. This research involved a case study in the Khiriwong community, the first CBET community (since 1996) in Thailand, through the application of ethnographic techniques. The findings reveal that since the notion of CBET relies heavily on aspects of community participation, cohesion, forest guardianship, self-reliance and sustainability, all of which are part of the picturesque ideal of romanticism, the community itself becomes associated with the identity, subject to the national policy and the expectations of external stakeholders, which eventually fall into the commodification of staged authenticity.